An analytica study of sand drain - Yong, K.S (University Malaysia Sarawak, UNIMAS., 2004)
In the present parametric study, time required for consolidation of clay layer is estimated with different configurations of sand drains. Diameter and spacing of sand drains are varied. Sand drains are arranged in triangular and rectangular pattern.